Impact of historical conflict on FDI location and performance: Japanese investment in China - Gao, Gerald Yong; Wang, Danny Tan; Che, Yi (Journal of International Business Studies, 2018)
Historical relations between countries bring important explanatory power for foreign direct investment (FDI) decisions, yet little is known on whether a home–host country relation exhibits heterogeneous effects on FDI across the country’s subnational regions. In this study, we examine the long-term impact of historical conflict on FDI location choices and performance. Using a sample of 8,646 Japanese FDI in China, we show that civilian casualties in different provinces of China during the Second Sino–Japanese War exert deterring effects on Japanese FDI location choices. Furthermore, we demonstrate that civilian casualties negatively affect Japanese FDI performance and political capital accumulation strategies, in the forms of excessive tax payment and local employment, can reduce this negative effect. This study contributes to the discussion on how within-country differences of historical factors affect FDI location decisions and performance. The findings on firms’ political capital accumulation strategies also provide important implications for FDI operation in an environment characterized by historical animosity.